THE EFFECT OF NEW PRODUCT DEVELOPMENT ON ORGANIZATIONAL PERFORMANCE - Daniel Amente KENEA (Annals of the University of Craiova for Journalism, Communication and Management)
New product development has become a potentially valuable way of securing a competitive advantage by improving organizational performances. Fundamentally, a firm fulfills this purpose through its products. The main purpose of this research is to assess the effect of new product development on organizational performance in the case of biscuit manufacturing companies found in Addis Ababa. A Quantitative research approach, descriptive research design, and cross-sectional field survey were used for this study. The probability sampling technique specifically the stratified random sampling method was applied in order to select sample respondents from the total population of 268. Primary data was collected using a structured questionnaire. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (Pearson correlation and multiple linear regression) with the help of SPSS Version 20.0. The result indicated that three of the independent variables such as product quality, product size, and product design have a moderate and positive relationship and; significantly affect organizational performance. Whereas, a product line which is the fourth independent variable has a weak relationship and insignificant effect on the performance of target organizations. Based on the findings, the researcher recommends biscuit manufacturing firms improve the quality of their product, and respond to the dynamic changes in customers’ needs in product size and product design through the introduction of new products to improve the performance of their organization.